THE INFLUENCE OF PRICE PERCEPTION, PROMOTION, AND ONLINE CUSTOMER REVIEW ON CONSUMER BUYING INTEREST IN LAZADA E COMMERCE IN PADANG UTARA DISTRICT - Magdalena, Maria; Zusmawati, Zusmawati; Algusri, Jeki; Fernos, Jhon; Rozi, Fakhrur (Jurnal Apresiasi Ekonomi, 2023)
ABSTRACTThis study has a problem formulation, namely whether price perception affects consumer buying interest in Lazada e-commerce and whether promotion affects consumer buying interest in Lazada e-commerce and whether online customer reviews affect consumer buying interest in Lazada e-commerce. And this study aims to determine whether price perceptions, promotions, and online customer reviews have an effect on consumer buying interest in Lazada e-commerce. The research method used is the Explanatory Research method. The sample obtained is 80 respondents. Data analysis used multiple linear regression analysis, classical assumption test, and hypothesis testing. The results showed that the price perception variable partially had a positive and significant effect on consumer buying interest in Lazada e-commerce. While the promotion variable partially has a positive and significant effect on consumer buying interest in Lazada e-commerce. And the online customer review variable partially has a positive and significant effect on consumer buying interest in Lazada e-commerce.Keywords: Buying Interest, Price Perception, Promotion, Online Customer Review